Simultaneous Determination of Aegeline and Six Coumarins from Different Parts of the Plant Aegle marmelos Using UHPLC-PDA-MS and Chiral Separation of Aegeline Enantiomers Using HPLC-ToF-MS - Avula, Bharathi; Chittiboyina, Amar G.; Wang, Yan-Hong; Sagi, Satyanarayanaraju; Raman, Vijayasankar; Wang, Mei; Khan, Ikhlas A. (Planta Medica, 2016)
A fast UHPLC-PDA method was developed for the simultaneous analysis of one alkaloid, aegeline, and six coumarins, viz., umbelliferone, scopoletin, marmesinin, 8-hydroxypsoralen, angelicin, and marmelosin, from the leaf, fruit, root, and bark of Aegle marmelos. The UHPLC method was validated for linearity, accuracy, repeatability, limits of detection and limits of quantification. The linearity range (r2 > 0.99) of the seven compounds was found to be 0.5–250 µg/mL, and the limits of detection and limits of quantification for the seven compounds were found to be 0.1 and 0.5 µg/mL, respectively. The developed UHPLC method is simple, fast, and especially suitable for quality control analysis of coumarins and aegeline from A. marmelos and commercial dietary supplements. Single quadrupole mass spectrometry was used for the identification and confirmation of coumarins and aegeline from different plant parts and dietary supplements. In addition, a novel chiral HPLC-ToF-MS method was developed for the resolution of aegeline enantiomers. By applying this chiral method, the distribution of enantiomers of aegeline from different parts of A. marmelos and aegeline-containing dietary supplements is reported for the first time.
Keywords: Aegle marmelos; Rutaceae; aegeline; coumarins; UHPLC-PDA-MS; HPLC-ToF-MS; chiral separation